The Effect of Guided Writing Method Assisted by Flash Card Media on Learning Motivation to Write Descriptive Essays in Class IV Elementary School Students - Rini Anriani; Sulfasyah Sulfasyah; Muhammad Akhir; Rosleny Babo (Buana Pendidikan, 2023)
This study aims to determine the effect of the guided writing method assisted by flash card media on the learning motivation to write descriptive essays for fourth-grade elementary school students. This research is a quasi-experimental design. The research design used was The Matching-Only Pretest-Postest Control Group Design. The sample in this study was fourth-grade students at SDN No.87 Tamanroya, which consisted of 48 students. The data collection used is a test and questionnaire technique. Data were analyzed through descriptive and inferential analysis techniques. Based on the research results, it was found that the results of learning to write descriptive essays and students' learning motivation in the experimental class experienced a more significant increase than the control class. Based on the hypothesis test, it obtained a significant value of less than 0.05 so it can be concluded that there is an effect of the guided writing method assisted by flash card media on the motivation to learn to write descriptive essays for fourth-grade students of SD SDN No.87 Tamanroya Kec. Galesong Utara, Kab.Takalar.